Features of technical and tactical actions of highly skilled athletes when swimming a distance of 100 meters by front crawl - Pilipko, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to determine the features of technical and tactical actions of highly skilled athletes when swimming a distance of 100 meters by front crawl.